A valid option for asthma control: Clinical evidence on efficacy and safety of fluticasone propionate/formoterol combination in a single inhaler. (October 2015) - Latorre, M.; Paggiaro, P.; Canonica, W.; Foschino, M.P.; Papi, A.
Abstract: A good level of asthma control improves the quality of life of asthmatic patients and may prevent future risk in term of exacerbations and decline of pulmonary function. However, in a real-life setting, several factors contribute to generally low compliance to the treatment. A rapid-onset, long-lasting medication with few adverse effects may contribute to improve adherence to therapy, along with an effective patient education and a good physician-patient communication. Many clinical studies demonstrated the comparable efficacy of the new fluticasone propionate/formoterol (FP/F) combination in a single inhaler to other combinations of inhaled corticosteroids and β2 agonists and the superiority of FP/F as compared to its individual components. Also the safety profile of this combination was encouraging in all studies, even at higher doses. By effectively and safely targeting both airway inflammation and smooth muscle dysfunction, the two pathological facets of asthma, and allowing the patient to adapt dose strength, FP/F combination in a single device represents a valid option to improve asthma control in patients with different levels of asthma severity.